La tonadilla a la Barcelona del darrer terç del Set-cents més enllà de la Casa de Comèdies. - PESSARRODONA, AURÈLIA (Scripta, 2014)
In eighteenth-century Barcelona the official monopoly of theatre was in the hands of the Hospital of the Holy Cross. But it is well know that the theatrical passion of the people of Barcelona went beyond the official theatre managed by this institution. The present article seeks to show the interest of the spectators of Barcelona in the tonadilla, a brief musical and theatral genre imported from Madrid. This interest went beyond the official theatre, with a significant trade of libretti and the possibility of a private practice. Therefore, we realize how this imported genre could become ingrained in the audience of Barcelona, touched deeply by lyric spectacles.